( 1 + i ) + ( 3 + 2 i ) + ( 5 + 3 i ) + … + ( x + y i )
The above shows a sum of an arithmetic progression with first term 1 + i and a common difference 2 + i , where i = − 1 .
The final term of this sum is x + y i for real numbers x and y .
If this sum is equal to 2 5 0 0 + 1 2 7 5 i , submit your answer as x + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Perfect Solution
so what u need to know is ∑(1 to x) which is equal to 2500; by applying the formula for sum of the series i.e Sn = n/2 (2a+(n-1)d) =2500=n/2 (2(1)+(n-1)2) (since we are doing summation of 1+3+....) =2500=n/2 (2+2n-2) =2500=n/2 (2n) =2500=n^{2} implies that, n=50 so,An=a +(n-1)d = 1+ 49(2) =99 therefore x=99 and since yi is same as n=50 thus, 99+50=149
you don't need any knowledge of complex numbers....just simple AP...
In simpler terms, the sum of odd numbers is
S = 4 ( x + 1 ) 2 ⇒ 2 5 0 0 ( 4 ) = ( n + 1 ) 2 ⇒ 5 0 ( 2 ) = n + 1
∴ n = 9 9
well done !
n = 1 ∑ y ( 2 n − 1 + n i ) y ( y + 1 ) − y + 2 y ( y + 1 ) i 2 5 5 0 − y ⟹ y x ⟹ x + y = 2 5 0 0 + 1 2 7 5 i = 2 5 0 0 + 1 2 7 5 i = 2 5 0 0 = 5 0 = 2 y − 1 = 9 9 = 9 9 + 5 0 = 1 4 9 ⟹ 2 y ( y + 1 ) = 1 2 7 5 ⟹ y ( y + 1 ) = 2 5 5 0
Problem Loading...
Note Loading...
Set Loading...
Find a relation between the two sequences and then solve!
The function consists of two arithmetic progressions: One for the real part, and the other for the imaginary part. First: We divide the function into two different series:
S 1 = 1 + 3 + 5 + 7 . . . x
S 2 = 1 + 2 + 3 + 4 . . . y
Second: Since it's a finite arithmetic sequence, we can put an expression to find the sum of all values in "n" terms. (Here N is unknown)
The Expression of the sum of a finite arithmetic sequence is 2 n ( l a s t + f i r s t )
So the sum of S 1 = 2 n ( x + 1 ) = 2 5 0 0
Then, n = ( y + 1 5 0 0 0 ) (1)
The sum of S 2 = 2 n ( x + 1 ) = 1 2 7 5
Third: We substitute the value of n in the expression of S 1 to get:
2 5 5 0 x + 2 5 5 0 = 5 0 0 0 y + 5 0 0 0 , (Put (1) instead of n and cross multiplicate) which is
5 1 x − 1 0 0 y = 4 9 (2)
Fourth: We will find a relation between the first and the second series, which is 2 ( S 2 ) k − ( S 1 ) k = 1 , which leads as to 2 y − x = 1 (3)
Fifth: Now we have two equations for the variables, let's do some math.
Multiply equation (3) by 5 0
1 0 0 y − 5 0 x = 5 0 (4)
Get the sum of equation (4) and (2) x = 9 9
Substitute the value of x in equation (3)
y = 5 0
Sixth: Get the answer x + y = 1 4 9